Associações entre saúde mental e aptidão física em estudantes universitários: análises transversais do estudo piloto da coorte Unilife-M - Guimarães, Maria Eduarda Adornes (2024)
There is a high prevalence of symptoms for anxiety and depression among university students. Physical fitness appears to be associated with mental health in the general population, and the combination of physical fitness tests seems to exert an additive effect in protecting against mental health issues. However, it is still unknown if this association replicates in university students, a young population but in the peak age range for the onset of mental health problems. The present study aimed to assess cross-sectional associations between symptoms of anxiety and depression and physical fitness tests in university students (≥18 years) from six Brazilian universities. Participants took part in an online survey and physical fitness tests. Mental health was assessed at two levels: 1) the Level 1 cross-sectional Symptoms Scale of the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5), and 2) participants with mild or higher scores for anxiety or depression symptoms were directed to level 2 instruments through the General Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9), respectively. Physical fitness was assessed through handgrip strength test, vertical jump, and the 20m Shuttle Run test. Results for each test were classified into low and high fitness, according to the median of each gender. A variable for overall physical fitness, grouping individuals who reached the median in 1 or 2 and three tests, and a variable for the co-occurrence of anxiety and depression symptoms were created. Associations were tested through Poisson regression model with robust variance. The sample consisted of 196 university students (52.63% women; median age=21). Students above the median in 2 or 3 physical fitness tests were less likely to present depressive symptoms (PR= 0,53; 95%CI: 0,33 – 0,84) than students with low physical fitness. Students who jumped above the median of the sample had a lower risk of presenting depressive symptoms (PR= 0,65; 95%CI: 0,44 – 0,97), separately. Students with higher overall physical fitness were less likely to experience the co-occurrence of anxiety and depressive symptoms (PR= 0.43; 95%CI: 0,26 – 0,71). Higher levels of overall physical fitness are associated with a lower probability of experiencing depression symptoms in university students. However, the presented results are based on cross-sectional data, preventing the establishment of causal relationships.